La fabrique des reliques. Manipulations et production de sacré dans la clôture - Francesca Sbardella (Conserveries Mémorielles)
On the basis of ethnographic fieldwork which was conducted among some Carmelite and Augustinian monastic groups (in France and in Italy), the aim of the present paper is to investigate the nature of relic-objects from an anthropological perspective. These are probably one of the most significant reified examples of the so-called ‘sacred’ as tangible evidence in contemporary western societies. Considering the case of the remains of Breton Blessed Françoise d’Amboise (1427-1485), the analysis will be focused on the transformation process human remains undergo to be turned into relics, this process being implemented by specialised secluded nuns. A number of issues will be addressed, such as the types of relational processes and strategies (including protagonists, situations, material and ideological systems) that are most relevant for these objects to be assigned and preserve their sacred power.